2014
DOI: 10.1371/journal.pone.0099638
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation and the Prevention of Functional Disability in Older Japanese: The JAGES Cohort Study

Abstract: BackgroundWe examined the relationship between incident functional disability and social participation from the perspective of number of types of organizations participated in and type of social participation in a prospective cohort study.MethodThe study was based on the Aichi Gerontological Evaluation Study (AGES) Cohort Study data. We followed 13,310 individuals aged 65 years or older for 4 years. Analysis was carried out on 12,951 subjects, excluding 359 people whose information on age or sex was missing. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
263
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(306 citation statements)
references
References 27 publications
30
263
1
3
Order By: Relevance
“…On the other hand, some previous studies have suggested that hobbies or cultural activities decreased the risk of functional disabilities among older adults [6, 7]. The present study found significant longitudinal relationships between hobbies or cultural activities and reduced difficulties in ADL only among middle-aged women.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…On the other hand, some previous studies have suggested that hobbies or cultural activities decreased the risk of functional disabilities among older adults [6, 7]. The present study found significant longitudinal relationships between hobbies or cultural activities and reduced difficulties in ADL only among middle-aged women.…”
Section: Discussionsupporting
confidence: 45%
“…volunteering and community activities) help maintain ADL in older adults. For example, a 4-year longitudinal study in Japan reported that participation in hobby activities decreased the risk of functional disability among older adults [6]. Another Japanese study using 3-year longitudinal data reported that participation in hobby groups could effectively maintain older adults’ effectance, which represents higher-level functional capacity [7].…”
Section: Introductionmentioning
confidence: 99%
“…While studies on aging generally involve more women than men, the present review identified a number of studies with a higher proportion of men than women 9,16,21,26 . In addition, some studies investigated only women or only men 19,[28][29][30][31][32] . These aspects may influence the results presented by these studies especially in relation to the social engagement of the elderly persons.…”
Section: Discussionmentioning
confidence: 99%
“…While men tend to disengage from political and organizational activities and work, women discontinue community activities and volunteer work. This disengagement is most pronounced at age 75, and maybe influenced by common events in old age, such as widowhood, retirement, health problems, and functional decline 10,18,30,31,33,36,37 . Benjamins et al 7 observed that acute events such as hip fractures, cancer and cerebrovascular accidents compromise participation in social activities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to prevent functional disability (Kanamori et al, 2014) and improve self-rated health (Ichida et al, 2013) among communitydwelling older adults in Japan. Similarly, in Canada, a significant association was found between social roles, as a component of social participation, and quality of life among community-dwelling older adults with physical disabilities (Levasseur, Desrosiers, & Noreau, 2004).…”
Section: Introductionmentioning
confidence: 99%